The Prevalence of Vitamin D Deficiency Among Patients With Schizophrenia in Duhok City - Mohamed, Jamal B.; Haji, Sipan S. (Science Journal of University of Zakho, 2016)
The current cross sectional study, it was aimed to estimate the prevalence of Vitamin D deficiency among 110 patients with schizophrenia in Duhok city, who attended the psychiatric Clinic and Department of Azadi teaching hospital. Their total vitamin D level was measured and the result indicated that vitamin D is below the normal level in more than 76% and deficient in 47%.  Statistical analysis of the results showed the presence of a significant difference in incidences between male and female and there were significant increase with the duration of the disease. From the results of the present study concluded that vitamin D deficiency is common in this group of population and most of them were not screened or treated.
Keywords: Vitamin D Deficiency; Patients; Schizophrenia; Duhok